Organic geochemistry and mineralogy. I. Characterisation of organic matter associated with metal deposits - Greenwood, Paul; Brocks, J.; Grice, Kliti; Schwark, Lorenz; Jaraula, Caroline; Dick, Jeffrey; Evans, K (Elsevier Science BV, 2013)
As geochemical appraisals of mineral regions of commercial prospectivity evolve, the organic matter associated with metal rich ores has attracted greater attention. Petroleum basin and modern seafloor hydrothermal vent studies have suggested that organic matter can have a significant influence on the behaviour of mineralising fluids. There have been many isolated reports of certain organic compositional or morphological (e.g. pyrobitumen) features showing an apparent relationships with hydrothermal fluids or minerals, raising expectations that organic based parameters might be useful to mineral exploration. However, the understanding of organic–inorganic relationships in Earth systems is far from complete. For example, the detailed mechanics of the interaction of organics with hydrothermal fluids over geological time remain largely undefined. Organic geochemistry studies have traditionally involved the measurement and interpretation of the hydrocarbon composition of sedimentary rocks. Here we review the types of aliphatic hydrocarbons, aromatic hydrocarbons and metalloporphyrins often detected from organic geochemical investigations in mineral-rich regions. Such molecular data can be particularly diagnostic of biochemical sources and the palaeo-environments at the time mineral associated organic matter was deposited. Sub-surface trends of hydrocarbon alteration may also reflect major biogeochemical processes such as thermal maturity and biodegradation. Organic geochemistry data can also occasionally provide information about the nature (e.g., origin, composition, temperatures) and migration pathways of hydrothermal fluids and can make a contribution to holistic ore genesis models.Organic geochemistry data can also occasionally provide information about the nature (e.g., origin, composition, temperatures) and migration pathways of hydrothermal fluids and can make a contribution to holistic ore genesis models. The well preserved organic matter associated with the economic “Here's Your Chance” Pb–Zn–Ag Mine (Paleoproterozoic Barney Creek Formation, McArthur Basin, Australia) and the transition metal-rich Early Permian Kupferschiefer Formation (Germany–Poland) have attracted significant attention.A more detailed summary of the organic character of these deposits is provided to highlight the contribution organic geochemistry can make to understanding mineralisation processes. Most organic geochemical studies of highlymineralised regions, however, have not adequately addressed the significance of organic matter to mineralisation. A slightly different analytical focus than traditionally used for exploration appraisal of petroleum hydrocarbons may be required to properly evaluate the significance of organic species to the mobilisation, transport and deposition of oremetals. The characterisation and subsequent thermodynamicmodeling of organic substances and complexes within metalliferous hydrothermal systems will contribute to a better understanding of the nature and role of organic–inorganic fluids or other affiliated organics in ore systems.